Very low birth weight infant outcomes in a resource-limited setting: a five-year follow-up study - Kresnawati, Windhi; Pandie, Peter John; Rohsiswatmo, Rinawati (Frontiers in Pediatrics, 2025)
BackgroundPreterm birth and very low birth weight (VLBW) remain major contributors to neonatal morbidity and mortality, particularly in low-income settings such as Indonesia, where healthcare resources are limited. In response, the Ministry of Health introduced mentoring programs in 2014, followed by intensive neonatal training initiatives in 2015. These interventions substantially improved survival rates for LBW infants however, they face significant growth and developmental challenges. This study aims to investigate the growth and development of VLBW infants in remote area at five years of age.MethodData were collected retrospectively between September 2021 and May 2022 from children born between 2016 and 2017 with VLBW (<1,500 grams) at Biak Regional Hospital, Indonesia. Growth parameters, including stunting and wasting and developmental outcomes such as cerebral palsy, blindness, and developmental impairment or delays were assessed after 5 years of age for follow up assessment.ResultsAmong 78 identified infants with VLBW, 54 infants (69.2%) with a gestational age of <34 weeks were discharged alive between 2016 and 2017. Their gestational ages ranged from 27 to 33 weeks, with birth weights between 625 and 1,400 grams. Overall, 12 infants died before reaching one year of age while five died after one year. The 1-year survival rate was 77.8%, while 5-year survival rate was 68.5%. The incidences of stunting, wasting, cerebral palsy, and blindness were 32.1%, 46.4%, 21.4%, and 10.7%, respectively.ConclusionThe high prevalence of growth and developmental impairments highlights the need for sustained multidisciplinary efforts to improve long-term outcomes for VLBW infants. In resource-limited settings, the focus should extend beyond survival to ensure optimal growth and development of the children.